2016
DOI: 10.12669/pjms.325.10772
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of mifepristone combined withGestrinone on patients with endometriosis

Abstract: Objective:To evaluate the clinical therapeutic effects of mifepristone combined with gestrinone on patients with endometriosis.Methods:A total of 150 endometriotic patients treated in our hospital between January 2014 and December 2015 were randomly divided into a control group and a treatment group (n=75). The control group began to orally take gestrinone capsules on the second day after menstruation started (2.5 mg/time, twice/week). The treatment group orally took mifepristone tablets (12.5 mg/time, once/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Our data showed that mifepristone significantly decreased platelet count in serum of the adenomyosis patients. Therefore, the clinical results further proved that mifepristone was efficient in the treatment of adenomyosis-associated dysmenorrhea and the effect of treatment in adenomyosis is similar to endometriosis [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that mifepristone significantly decreased platelet count in serum of the adenomyosis patients. Therefore, the clinical results further proved that mifepristone was efficient in the treatment of adenomyosis-associated dysmenorrhea and the effect of treatment in adenomyosis is similar to endometriosis [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, drug and surgery are the main therapeutic strategies for EM caused infertility; although the surgery can reduce the pain, it also leads to infertility because of surgical trauma and easy relapse . Treatment of EM using TCM is routine and demonstrates the function of promoting fertility, alleviating pain, and preventing relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Резултатите показват подобряване на симптомите при жените, приемащи мифепристон от 5 мг и 10 мг, сравнено с тези, приемащи мифепристон 2,5 мг и плацебо. Друго проучване, включващо 150 жени с ендометриоза, разделени в две групи -едната приемаща гестринон, а другата комбинация от мифепристон и гестринон в продължение на 24 седмици, показва по-добро повлияване на дисменореята, диспареунията и тазовата болка при комбинираното лечение (71).…”
Section: селективни модулатори на прогестероновите рецептори (смпр)unclassified